Diversity, trait preferences, management and utilization of yams landraces (Dioscorea species): an orphan crop in DR Congo - Adejumobi, I.I.; Agre, A.P.; Onautshu, O.D.; Adheka, J.G.; Bambanota, M.G.; Monzenga, J.C.L.; Komoy, J.; Cipriano, I.M. (Springer, 2022)
Yam (Dioscorea spp.) is cultivated in many villages of DR Congo as a means to sustain food security and alleviate poverty. However, the extent of the existing diversity has not been studied in details thus, considered as an orphan. A survey covering 540 farmers in 54 villages was conducted in six major yam growing territories covering three provinces in DR Congo to investigate the diversity, management and utilization of yam landraces using pre-elaborate questionnaires. Subject to synonymy, a total of 67 landraces from five different species were recorded. Farmers’ challenges limiting yam production were poor tuber qualities (69%), harvest pest attack (7%), difficulty in harvesting (6%), poor soil status (6%). The overall diversity was moderate among the recorded yam germplasm maintained at the household level (1.32) and variability exist in diversity amongst the territories and provinces. Farmers’ in territories of Tshopo and Mongala provinces maintained higher level of germplasm diversity (2.79 and 2.77) compared to the farmers in territories of Bas-Uélé (1.67). Some yam landraces had limited abundance and distribution due to loss of production interest in many villages attributable to poisons contained hence, resulting in possible extinction. Farmers’ most preferred seed source for cultivation were backyard (43%) and exchange with neighboring farmers (31%) with the objective of meeting food security and generating income. In villages where yam production is expanding, farmers are relying on landraces with good tuber qualities and high yield even though they are late maturing. This study revealed the knowledge of yam landrace diversity, constraints to production and farmers’ preferences criteria as a guide for collection and conservation of yam germplasm for yam improvement intervention.